A sustainable synthesis of polyhydroxyalkanoate from stubble waste as a carbon source using Pseudomonas putida MTCC 2475 - Kukreti, Neha; Kumar, Pravir; Kataria, Rashmi (Frontiers in Bioengineering and Biotechnology, 2024)
Polyhydroxyalkanoates (PHAs) are biodegradable polymers that can be produced by microorganisms from lignocellulosic biomass. Cheap and easily available raw material such as corn stover waste has the potential to lessen the cost of PHA synthesis. In this research study, corn stover is utilized for sodium hydroxide alkali pre-treatment and optimization with central composite design (CCD) for high cellulose and low lignin followed by characterization using FT-IR, TGA and SEM. Design expert software performed further optimization of alkali pre-treated corn stover for high total reducing sugar (TRS) enhancement using CCD using Response surface methodology (RSM). The optimized condition by RSM produced a total reducing sugar yield of 707.19 mg/g. Fermentation using corn stover hydrolysate by Pseudomonas putida MTCC 2475 gave mcl-PHA detected through GC-MS/MS and characterization of PHA film by DSC, FTIR and NMR. Thus, this research paper focuses on using agriculture (stubble) waste as an alternative feedstock for PHA production.